Hi everyone, I really need help to prove this statement: (p→s) from( p→not q), (r→q )and (not r→s) Thanks
Follow Math Help Forum on Facebook and Google+
Originally Posted by eps hi everyone, i really need help to prove this statement: (p→s) from( p→not q), (r→q )and (not r→s) do not ever double post!
OUCH! That's telling him, Plato!
Originally Posted by HallsofIvy OUCH! That's telling him, Plato! OUCH! is correct. Two people spent time and effort to help with the other post. Wasting time is a shame.
View Tag Cloud